Dental clinical recommendations against COVID-19, according to scientific evidence - Cayo Rojas, César (2020)
The information presented gives an excellent historical description of the appearance and evolution of the Coronavirus disease 2019; describes precisely the taxonomic, biological and genomic characteristics of SARS-CoV-2 and provides us with updated epidemiological data that allows us to have a clear idea of how the virus is spreading worldwide. On the other hand, it emphasizes the importance of being prepared to fight against infectious diseases because this disease has a rapid evolution that results in fear not only in people in general but also in the health professionals who must necessarily be in direct contact with the patient, as in the case of the dentist. For this reason, we would like to specify certain dental clinical recommendations, based on the scientific evidence available up to now.